Acute and Post-traumatic Stress Disorder Symptoms in Mothers and Fathers Following Childbirth: A Prospective Cohort Study - Schobinger, Elisabeth; Stuijfzand, Suzannah; Horsch, Antje (Frontiers in Psychiatry, 2020)
Introduction Up to 30% of women view their childbirth as traumatic. This experience can lead to acute stress disorder or post-traumatic stress disorder. The negative impact of maternal post-traumatic stress disorder following childbirth reaches beyond the mother, potentially affecting her child's development and the couple's relationship. Research on paternal post-traumatic stress disorder following childbirth is scarce. Acute stress disorder is suggested to be an important predictor of post-traumatic stress disorder in mothers, but little is known about paternal acute stress disorder following childbirth. Furthermore, there is limited information about the comparison or relation of acute stress disorder and post-traumatic stress disorder following childbirth between parents. Aim [1] To compare the prevalence rates and severity of acute stress disorder and post-traumatic stress disorder symptoms between parents following childbirth by taking anxiety and depression symptoms, as well as obstetric variables and previous traumatic events into account and [2] To determine if acute stress disorder is a predictor of post-traumatic stress disorder. Method A prospective population-based design was used. N = 647 participants were recruited from future parents who attended appointments at the Obstetrics and Gynecology unit at a Swiss university hospital. Self-report questionnaires were used: Post-traumatic Diagnostic Scale in the third trimester of pregnancy (T1) and 1 month post-partum (T3), Acute Stress Disorder Scale at 1 week post-partum (T2), and Hospital Anxiety and Depression Scale at all time points. Obstetric and neonatal variables were retrieved from hospital records. Results At T2, 8.9% of mothers and 4.4% of fathers presented symptoms of acute stress disorder. At T3, 20.7% of mothers and 7.2% of fathers had symptoms of post-traumatic stress disorder. Acute stress disorder was a predictor of post-partum post-traumatic stress disorder (Odds ratio: 8.6, IC 95% [1.85; 40.42]). Depression symptoms was a significant confounder in the prediction of post-traumatic stress disorder following childbirth, but not anxiety or previous perinatal loss. Conclusion Little is known about parental differences in acute stress disorder and post-traumatic stress disorder symptoms following childbirth. Results indicate that both parents may suffer from acute stress disorder and post-traumatic stress disorder symptoms after childbirth and that acute stress disorder is a predictor of post-traumatic stress disorder after childbirth for both parents. Sensitization of maternity staff to these results may assist in earlier identification of and appropriate treatment for at-risk parents.